2019
DOI: 10.7150/jca.36614
|View full text |Cite
|
Sign up to set email alerts
|

A perspective profile of ADCY1 in cAMP signaling with drug-resistance in lung cancer

Abstract: Adenylate cyclase 1 (ADCY1 or AC1) is a member of ADCY superfamily and was primarily found to be expressed in the brain. ADCY1 is responsible for catalyzing ATP to cyclic AMP (cAMP). As a secondary messenger, cAMP can regulate plenty of cellular activities. cAMP can perform its regulation in cellular transport through the binding to cAMP dependent protein kinases (PKAs), cAMP-activated guanine exchange factors (EPACs) and cyclic nucleotide-gated channels functioning in transduction of sensory signals (CNGs). L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 84 publications
(80 reference statements)
0
26
0
Order By: Relevance
“…Further studies are needed to determine whether CRTC3 induces higher expression of adipogenic genes in vivo . In addition, CRTC3 regulates the expression of ADCY family that affects the synthesis of cAMP from ATP and links the regulation of adipose tissue development to adiposity [ 43 , 44 ]. In addition, CRTC3 overexpression also increased the expression of FA metabolism-related genes including the ACOX1 , FADS1/2 and ELOVL3/6 .…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to determine whether CRTC3 induces higher expression of adipogenic genes in vivo . In addition, CRTC3 regulates the expression of ADCY family that affects the synthesis of cAMP from ATP and links the regulation of adipose tissue development to adiposity [ 43 , 44 ]. In addition, CRTC3 overexpression also increased the expression of FA metabolism-related genes including the ACOX1 , FADS1/2 and ELOVL3/6 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was found that cAMP signaling plays an important role in tumor progression and therapy. [27][28][29][30][31] Therefore, it is speculated that PDE7B may play a role in tumorigenesis through regulating the cAMP levels. Indeed, a number of studies have shown that PDE7B is deregulated in various cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the DEG PRL was identified, which was enriched in the most pathways related to hypothalamic function and follicular development, including the neuroactive ligand–receptor interaction, PI3K–Akt, and prolactin signaling pathways. PRL is demonstrated to be expressed in the hypothalamus ( Roselli et al, 2008 ; Zou et al, 2019 ). That is, hypothalamic PRL mainly functions in the transmission of neural signals and the synthesis and secretion of reproductive hormones.…”
Section: Discussionmentioning
confidence: 99%